Are Tax Effects Important in the Long‐Run Fisher Relationship? Evidence from the Municipal Bond Market - Crowder, William J.; Wohar, Mark E. (Journal of Finance, 1999)
Are nominal bonds appropriately discounted for taxes? Empirical estimates of the response of nominal interest rates to changes in inflation, the Fisher effect, have failed to produce a definitive answer. Four reasons have been put forward as possible explanations: (i) Tobin effects, (ii) fiscal illusion, (iii) peso problems, and (iv) different estimators. Utilizing data on taxable and tax‐exempt bond interest rates and several different estimators, we find that the Fisher effect estimates are always larger for the taxable bond relative to the tax‐exempt bond, suggesting that fiscal illusion and different estimators cannot account for the previous results.